Hubungan Antara Kematangan Emosi Dengan Penyesuaian Diri pada Remaja - Usop, Dwi Sari (Anterior Jurnal, 2013)
Adolescence is a unique time in the phase of teenage life, where a person who has entered adolescence has a unique characteristic. With these distinctive characters, teenagers are required to be able to adjust well to the surrounding individuals. However, not all teenagers have a good adjustment. This has become one of the obstacles in the lives of teenagers to lead a healthy life. One other obstacle is the problem of emotional maturity, because there are still many teenagers who do not have good emotional maturity. This study aims to determine the relationship between emotional maturity and adjustment at SMPN 19 Surabaya. The study population was all students of class VIII, totaling 261 people and a sample of 106 students. The sampling technique used in this study is non random sampling with data collection techniques in the form of questionnaires arranged on a Likert scale. The study showed very significant results, where the value of r = 0.809 with p = 0.000 (p <0.010). This means that the proposed hypothesis is accepted. Emotional maturity has a very significant relationship with adapting to adolescents at SMPN 19 Surabaya